2015
DOI: 10.5935/1806-0013.20150008
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation in fibromyalgia: effects on pain and quality of life evaluated clinically and by brain perfusion scintigraphy

Abstract: BACKGROUND AND OBJECTIVES: Transcranial Direct Current Stimulation is a neuromodulation method to treat neuropsychiatric and other diseases. This study aimed at evaluating the effect of this technique on pain and quality of life of fibromyalgia patients, in addition to studying brain images by Brain Perfusion Scintigraphy before and after procedures. METHODS: Prospective, double-blind, randomized, controlled study with parallel arms evaluated clinically and by CT scan with single photon emission (Brain Spect).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 16 publications
1
31
0
2
Order By: Relevance
“…We used 1 mA to facilitate blinding of the participants as the efficacy of blinding with intensities higher than this is uncertain (Riberto et al., ; Kessler et al., ; O'Connell et al., ; Palm et al., ); however, this may have limited the physiological impact of active tDCS. Other studies using 1 mA intensity have reported a significant reduction in pain (Fenton et al., ; Antal et al., ; Sakrajai et al., ; Jales Junior et al., ), and there were individuals within our active group who had a sustained and clinically meaningful reduction in pain. Another limitation of our study may be the heterogeneity of the participants, who presented with a variety of aetiologies underlying their neuropathic pain, and the potential for differences in medication use between groups to influence the outcomes.…”
Section: Discussionmentioning
confidence: 52%
“…We used 1 mA to facilitate blinding of the participants as the efficacy of blinding with intensities higher than this is uncertain (Riberto et al., ; Kessler et al., ; O'Connell et al., ; Palm et al., ); however, this may have limited the physiological impact of active tDCS. Other studies using 1 mA intensity have reported a significant reduction in pain (Fenton et al., ; Antal et al., ; Sakrajai et al., ; Jales Junior et al., ), and there were individuals within our active group who had a sustained and clinically meaningful reduction in pain. Another limitation of our study may be the heterogeneity of the participants, who presented with a variety of aetiologies underlying their neuropathic pain, and the potential for differences in medication use between groups to influence the outcomes.…”
Section: Discussionmentioning
confidence: 52%
“…We included 38 new studies in this review. Of these, 12 studies (355 participants) investigated only rTMS (Boyer 2014; Dall'Agnol 2014; de Oliveira 2014; Jetté 2013; Malavera 2013; Medeiros 2016; Nardone 2017; Nurmikko 2016; Tekin 2014; Umezaki 2016; Yagci 2014; Yilmaz 2014), 22 studies (772 participants) investigated tDCS (Ahn 2017; Ayache 2016; Bae 2014; Brietzke 2016; Chang 2017; Donnell 2015; Fagerlund 2015; Hagenacker 2014; Harvey 2017; Hazime 2017; Jales Junior 2015; Khedr 2017; Kim 2013; Lagueux 2017; Luedtke 2015; Mendonca 2016; Ngernyam 2015; Oliveira 2015; Sakrajai 2014; Souto 2014; Thibaut 2017; Volz 2016) one study (36 participants) investigated tDCS and rTMS (Attal 2016), two studies (16 participants) investigated tRNS (Curatolo 2017; Palm 2016) and one study investigated RINCE (Deering 2017, 46 participants). Overall this updated review included 94 studies (2983 participants), with 42 trials of rTMS (1101 participants), 36 trials of tDCS (1073 participants), 11 studies of CES (572 participants), one study (36 participants) of both rTMS and tDCS, two studies of RINCE (137 participants) and two studies of tRNS (36 participants).…”
Section: Resultsmentioning
confidence: 99%
“…For CES there were eight parallel studies (Gabis 2003; Gabis 2009; Katsnelson 2004; Lichtbroun 2001; Rintala 2010; Tan 2006; Tan 2011; Taylor 2013), and three cross‐over studies (Capel 2003; Cork 2004; Tan 2000), of which we considered two as parallel studies, with only the opening phase of the study considered in this review because subsequent phases were unblinded (Capel 2003; Cork 2004). For tDCS there were 26 parallel studies (Ahn 2017; Bae 2014; Brietzke 2016; Chang 2017; Donnell 2015; Fagerlund 2015; Fregni 2006a; Fregni 2006b; Harvey 2017; Hazime 2017; Jales Junior 2015; Khedr 2017; Lagueux 2017; Kim 2013; Luedtke 2015; Mendonca 2011; Mendonca 2016; Mori 2010; Oliveira 2015; Riberto 2011; Sakrajai 2014; Soler 2010; Souto 2014; Thibaut 2017; Valle 2009; Volz 2016), and 10 cross‐over studies (Antal 2010; Ayache 2016; Boggio 2009; Fenton 2009; Hagenacker 2014; Jensen 2013; Ngernyam 2015; Portilla 2013; Villamar 2013; Wrigley 2014), of which we considered one as a parallel study with only the opening phase of the study considered in this review due to excessive attrition after the first phase (Antal 2010). One study of tRNS (Palm 2016) used a cross‐over design and one a parallel design (Curatolo 2017) and both RINCE studies used a parallel design (Deering 2017; Hargr...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations